Analysis of Science Literacy Difficulties of Students at Madrasah Al-Urwatul Wutsqaa Islamic Boarding School - Hikman, Mawar; Helmi; Usman (Journal of Physics Education : Review and Research, 2025)
This research aims to analyze the scientific literacy difficulties of class The method used was ex post facto research with a sample of 77 students. Data was collected through multiple choice tests that have been validated using the Gregory test. This research focuses on three aspects of scientific literacy, namely the scientific competency aspect, the content aspect, and the scientific context aspect. The research results show that the overall scientific literacy score of students is in the high category with an average value of (19,96). Distribution of average scores for each aspect, the scientific competency aspect is in the high category with an average score (6,49), the content aspect is also in the high category with an average score (6,68), while the context aspect is in the sufficient category with an average score (4,19). Based on these results, the aspect of scientific competence which is in the high category shows that the majority of students do not experience difficulty in identifying scientific issues and explaining phenomena scientifically. The content aspect which is also in the high category shows that students are able to understand and do not experience difficulties in understanding problems in terms of content and procedural aspects. However, the context aspect which is in the sufficient category shows that there are still difficulties in connecting scientific concepts with real phenomena.